2012
DOI: 10.1002/app.38619
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of sorbitol‐doped poly(vinyl alcohol)–poly(acrylamide‐co‐acrylic acid) polymer membranes

Abstract: Solid polymer membranes from poly(vinyl alcohol) (PVA) and poly(acrylamide‐co‐acrylic acid) (PAA) with varying doping ratios of sorbitol were prepared using the solution casting method. The films were examined with Fourier transform infrared spectroscopy, thermogravimetric analysis, differential scanning calorimetry, and AC impedance spectroscopy. The impedance measurements showed that the ionic conductivity of PVA–PAA polymer membrane can be controlled by controlled doping of sorbitol within the polymer blend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Poly(vinyl alcohol) (PVA) is a water‐soluble synthetic polymer that is formed from a hydrolysis process of poly(vinylacetate) . It has high chain flexibility as well as high concentration for the polar groupsaccording to the polymer's molar mass.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Poly(vinyl alcohol) (PVA) is a water‐soluble synthetic polymer that is formed from a hydrolysis process of poly(vinylacetate) . It has high chain flexibility as well as high concentration for the polar groupsaccording to the polymer's molar mass.…”
Section: Introductionmentioning
confidence: 99%
“…In previous investigations, the influences of blending PVA with different ratios of plasticizers on electrical, structural, and mechanical properties of the membranes were examined. The studies demonstrated that the addition of plasticizers to PVA enabled the control of its electrical conductivity and decreased the interaction among the macromolecules that increased the flexibility of its membranes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The preparation of the semiconducting blend polymer is described by Josh et al (2013). Briefly, poly-vinyl alcohol (PVA) and poly-acrylic acid (PAA) with average molecular weights of 61,000 g/mol and 5,000,000 g/mol, respectively, were used.…”
Section: Energy Storagementioning
confidence: 99%